Bagaimana Leader Autonomy Support Dapat Meningkatkan Perilaku Inovatif pada Karyawan? - Bella Ulfa; Alice Salendu (Jurnal Ilmu Perilaku, 2021)
Innovative behavior has an important influence on the development, excellence, and success of an organization. Therefore, it is important to identify the antecedents of employees' innovative behavior. This study aims to investigate the moderating effect of ambidextrous organization culture in the relationship between leader autonomy support (LAS) and innovative behavior. Data were collected using an online survey (platform surveymonkey). Participants of this study were 117 employees in Jakarta with a tenure minimum of 1 year. Convenience sampling was used as the sampling technique. Data were analyzed by moderation model technique (PROCESS model 1) using Hayes PROCESS on SPSS software. Results showed that leader autonomy support significantly predict innovative behavior (b= 0.50, confidence interval [CI] [0.17, 0.83]). While ambidextrous organization culture significantly moderate the influence of leader autonomy support on innovative behavior (b=0.07, [CI][0.03, 0.12]). The results showed that ambidextrous organization culture moderated the correlation between LAS and innovative behavior. Leader’s support for employee’s innovative behavior should be strengthened and companies are expected to put more effort in understanding the role of situational factors (i.e., ambidextrous organizational culture) in employee’s innovative behavior.